Implementation of motion planning and active force control to a virtual wheeled mobile robot - Tang, Howe Hing (2004)
The research focuses on the development of a virtual wheeled mobile robot (WMR) simulator that integrates the essential aspects of motion planning, motion control and virtual reality (VR) technique. The developed simulator may serve as a virtual testbed for the repetitive experimentation of the proposed mobile robot control scheme within a specified workspace or layout. The motion path planning is based on the A*heuristic search algorithm with a specific reference to the sixelementary jumps graph for the generation of a nonholonomic global collision-free path environment. A robust active force control (AFC) strategy is incorporated as the WMR motion controller that can accommodate effective disturbance compensation control action in order to produce accurate trajectory tracking task even in the wake of the modelled disturbances. A trajectory planner has been deliberately introduced as the interface between the motion planner and the motion controller. Later, a VR technique is applied to create the virtual environment (VE) that effectively integrates the main elements and transforms the system into a virtual WMR simulator with the added features that will enable researcher to perform experimentation of the mobile robot. A case study is furnished in the research study taking into account a computer integrated manufacturing (CIM) layout in which the proposed mobile robot is supposed to navigate. A rigorous simulation study is performed to demonstrate the effectiveness of the proposed system. Results clearly indicate the successful realization as well as implementation of the developed virtual WMR simulator in which the WMR has been conclusively shown to be very stable, robust and accurate in its tracking ability.